Effect of increased dietary protein on tolerance to intensified training - Witard, O. C.; Jackman, S. R.; Kies, A. K.; Jeukendrup, A. E.; Tipton, K. D. (Medicine & Science in Sports & Exercise, 2011)
Purpose: The purpose of the present study was to examine the effect of increased protein intake on short-term decrements in endurance performance during a block of high-intensity training.